DNA-sequence variation among Schistosoma mekongi populations and related taxa; phylogeography and the current distribution of Asian schistosomiasis. - Stephen W Attwood (Public Library of Science (PLoS), 2008)
Background Schistosomiasis in humans along the lower Mekong River has proven a persistent public health problem in the region. The causative agent is the parasite Schistosoma mekongi (Trematoda: Digenea). A new transmission focus is reported, as well as the first study of genetic variation among S. mekongi populations. The aim is to confirm the identity of the species involved at each known focus of Mekong schistosomiasis transmission, to examine historical relationships among the populations and related taxa, and to provide data for use (a priori) in further studies of the origins, radiation, and future dispersal capabilities of S. mekongi. Methodology/principal findings DNA sequence data are presented for four populations of S. mekongi from Cambodia and southern Laos, three of which were distinguishable at the COI (cox1) and 12S (rrnS) mitochondrial loci sampled. A phylogeny was estimated for these populations and the other members of the Schistosoma sinensium group. The study provides new DNA sequence data for three new populations and one new locus/population combination. A Bayesian approach is used to estimate divergence dates for events within the S. sinensium group and among the S. mekongi populations. Conclusions/significance The date estimates are consistent with phylogeographical hypotheses describing a Pliocene radiation of the S. sinensium group and a mid-Pleistocene invasion of Southeast Asia by S. mekongi. The date estimates also provide Bayesian priors for future work on the evolution of S. mekongi. The public health implications of S. mekongi transmission outside the lower Mekong River are also discussed.